أهمية استغلال الطاقات المتجددة في تعزيز التنمية المستدامة في الجزائر - طالبي, أحمد زكريا; مباركي, مروان (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الورقة البحثية إلى دراسة أهمية التحول من استخدام الطاقات التقليدية الناضبة وما تخلفه من ضرر على مختلف النواحي الاقتصادية والاجتماعية والبيئية، إلى استغلال الطاقات المتجددة المستدامة النظيفة في تعزيز تحقيق أهداف التنمية المستدامة من مختلف جوانبها الاجتماعية والاقتصادية والبيئية مع الإشارة إلى تحديات الجزائر في استغلال الطاقات المتجددة. The aim of this article is to study the importance of moving from the use of the traditional energies phase with its economic, social and environmental impacts to the exploitation of renewable and sustainable and clean energies to promote the achievement of the objectives of the sustainable development in its various aspects; social, economic and environmental issues by highlighting the challenges of the exploitation of renewable energies in Algeria.
The Importance Of Exploiting Renewable Energies In Promoting Sustainable Development In Algeria
مقال
Keywords: الطاقة المتجددة، التنمية المستدامة، الطاقة المتجددة في الجزائر; renewable energy, sustainable development, renewable energy in Algeria